Urinary tract infection: is it time for a new approach considering a gender perspective and new microbial advances? - González, María José; Robino, Luciana; Zunino, Pablo; Scavone, Paola (Frontiers in Urology, 2024)
Urinary tract infections (UTIs) are among the most common bacterial infections in humans, particularly affecting women, with significant clinical and socioeconomic impacts. Despite advances in medical research, the diagnostic criteria for UTI have remained practically unchanged since Kass’s seminal work, emphasizing the need for a reevaluation in light of new scientific insights. Recent studies have highlighted the importance of the urobiome, a previously underappreciated community of microorganisms within the urinary tract (UT), and its role in maintaining urogenital health. The gut-bladder axis has emerged as a critical pathway in understanding UTI as a dysbiosis, where imbalances in the microbial community and its relation with the host contribute to infection susceptibility. This review explores the evolving definitions and diagnostic challenges of UTI, particularly in women, and examines the implications of recent discoveries on the urobiome and the gut-bladder axis. Additionally, we discuss the potential of novel therapeutic strategies to restore microbial balance, offering a promising avenue for the therapeutic management of UTIs.